Long-Term Outcome of Mustard/Senning Correction for Transposition of the Great Arteries in Sweden and Denmark. Issue 8 (25th August 2015) - Vejlstrup, Niels; Sørensen, Keld; Mattsson, Eva; Thilén, Ulf; Kvidal, Per; Johansson, Bengt; Iversen, Kasper; Søndergaard, Lars; Dellborg, Mikael; Eriksson, Peter
<x xml:space="preserve">Abstract</x> Background— The atrial switch operation, the Mustard or Senning operation, for the transposition of the great arteries (TGA) was introduced in the late 1950s and was the preferred surgery for TGA until the early 1990s. The Mustard and Senning operation involves extensive surgery in the atria and leaves the right ventricle as the systemic ventricle. The Mustard and Senning cohort is now well into adulthood and we begin to see the long-term outcome. Methods and Results— All the 6 surgical centers that performed Mustard and Senning operations in Sweden and Denmark identified all operated TGA patients. Information about death was obtained in late 2007 and early 2008 from the Danish and Swedish Centralised Civil Register by using the patients' unique national Civil Registration Numbers. Four hundred sixty-eight patients undergoing the atrial switch operation were identified. Perioperative 30-day mortality was 20%, and 60% were alive after 30 years of follow-up. Perioperative mortality was significantly increased by the presence of a ventricular septal defect, left ventricular outflow obstruction, surgery early in the Mustard and Senning era. However, only pacemaker implantation is predictive of long-term outcome (hazard ratio, 1.90; 95% confidence interval, 1.05–3.46, P=0.04), once the TGA patient has survived the perioperative period. The risk of reoperation was correlated to the presence of associated defects and where the first Mustard/Senning operation was performed. Conclusions— The long-term survival of patients with Mustard and Senning correction for TGA appears to be primarily determined by factors in the right ventricle and tricuspid valve and not the timing of or the type of surgery in childhood. Cardiac function necessitating the implantation of a pacemaker is associated with an increase in mortality.